The Inheritance of Daralgazi: an Aristocratic Property in the Vega of Granada - Sandra SUÁREZ GARCÍA (Studia Historica. Historia Medieval, 2019)
In this essay we will analyze the characteristics of the inheritance of Daralgazi, located in the Vega of Granada, which Sancho de Castilla receives from the Catholic Monarchs in 1494, through a mercy granted for his merits in the War of Granada. Daralgazi is a property that passes from the holding of the «Moorish queens» to the hands of the Castilian-Aragonese monarchs during the time of the capitulations. We will focus on the characteristics of this property, the mention of it in other kinds of sources, and their nature and location. To sum up, all this topic will be inserted in the debate of the change of aristocratic property in the period of Conquest.